Downregulated Expression of miRNA-130a-5p Aggravates Hepatoma Progression via Targeting PTP4A2. (28th December 2021) - Shi, Longqing; Wang, Fengbo; Zhang, Yue; Yang, Yue; Qu, Zheng; Sun, Donglin
Abstract : Background . Hepatoma is a leading cause of death worldwide, with high metastasis and recurrence rates. The aberrant expression of miRNA-130a-5p is involved in the development and progression of various cancers. However, there are no studies investigating the role of miRNA-130a-5p in hepatoma. The present study is aimed at clarifying the functional role of miRNA-130a-5p in hepatoma progression. Methods . The expression levels of miRNA-130a-5p in hepatoma tissues and cell lines were detected by qRT-PCR assays. Bioinformatic analysis, gain-/loss-of-function experiments, and luciferase activity assays were conducted to verify whether miRNA-130a-5p is targeted by protein tyrosine phosphatase 4A2 (PTP4A2). The functions of miRNA-130a-5p and PTP4A2 in hepatoma were determined by cell proliferation assays. Results . The expression of miRNA-130a-5p was downregulated in hepatoma tissues and was related to poor prognosis. However, the expression level of PTP4A2 was contradictory to that of miRNA-130a-5p, and PTP4A2 upregulation could aggravate hepatoma progression. The ectopic overexpression of PTP4A2 promoted hepatoma cell proliferation in vitro, which could be reversed by miRNA-130a-5p. Conclusions . Our study implies that miRNA-130a-5p, which is downregulated in hepatoma tissues, can suppress hepatoma cell proliferation via targeting PTP4A2.